A Content Analysis of e-Government Practice in Indonesia: The Case of Pontianak Municipality - Rahman, Syaiful (FIA UB, 2018)
This paper aims to describee how the implementation of E-Government within public service provision in Pontianak City, West Kalimantan, Indonesia. This paper empirically investigated the implementation of e-Government by conducting a content analysis of the website portals developed by agencies under the jurisdiction and direction of Pontianak Municipality. The findings of the paper indicate that most of websites developed by government agencies vary in terms of e-government categories consisting of G2C, G2B, G2G, G2N, and G2E. In addition, those are in enhanced presence stage that means only employ e-Government to provide dynamic, specialized and regularly updated information. Based on the results, this paper suggests that the government needs to develop standards for agencies in terms of website design to optimize and promote the sustainable development through the benefits offered by e-Government. Despite having an important contribution for academics and practitioners, this study produced rather limited results because the author conducted the research only on agencies in a local government sphere, that is Pontianak Municipality. Therefore, it is highly recommended for further studies to do the research on a wider scope.